PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH SPONSORSHIP TERHADAP NIAT BELI MOTOR YAMAHA DI KOTA DENPASAR - Wikramayana, I Gusti Putu Sidhi; Satria Pramudana, Komang Agus (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
Sponsorship is one way of marketing that is growing rapidly nowadays. It is aimed to introduce company’s product to consumers. This way become popular by hope will improve consumer purchasing intention. During the process of sponsorship, good information products will create brand image. This research aims to find out the influence between sponsorship to purchasing intention with brand image as a mediation variable. Reliazing the potential market of two wheels vehicles, especially the motorbikes in Indonesia, and then this research raising the topic with sponsorship, brand image and purchasing intention as the objects. Respondens are them who in addition to motorbikes unless Yamaha in Denpasar City of period 2014. The survey conducted by spreading questionnaire measured by likert’s scale. Data analysed by statistical descriptive and statistics descriptive inferential with regression in accordance with the Baron and Kenny steps accompanied sobel test to test hyphotesis that is formulated. The results of this research showed that variable brand image capable of being mediated the influence between sponsorship and purchasing intention of consumers.
Keywords: sponsorships, brand image, purchasing intention